Geoscience education and development on the needs (or lack of) of environmental input - Hasan, M.A. (1983)
Today, more than ever before, there is an increased awareness of the importance of geoscience education and its relationship to human welfare. Teaching of geoscience in most of the developing countries a fairly new innovation. The rapidly diminishing mineral and energy resources, rising populations, expanding cities and environmental problems are but a few of the problems that today's geoscientists are asked to address themselves to. It can be argued the relatively recent social, cultural and scientific changes have begun to affect the geosciences to the extent that new and more innovative approaches to geoscience education are not only desirable but has become a necessity. The writer here feels that more environmental inputs should be introduced in the present geoscience curriculum. The needs of these environmental inputs are cited with special examples of environmental impacts of mining industries. Ways and means of introducing these environmental inputs are also described in this presentation.